Are the 6-minute walk test and the 2-minute walk test equivalent in acute and subacute stroke survivors in Belgium and Vietnam: a multicultural study - Duy Thanh Nguyen; Chloé Sauvage; Claire Questienne; Michel Duchène; Duan Van Nguyen; Dung Tan Nguyen; Massimo Penta (Journal of Rehabilitation Medicine, 2025)
Objective: To test the equivalence of the 6-minute walk test and the 2-minute walk test in stroke survivors in a multicultural setting, focusing on reliability, performance, and associations with clinical and anthropometric factors.